2022
DOI: 10.3390/su141711031
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Evolution and Influencing Mechanism of Traffic Dominance in Qinghai-Tibet Plateau

Abstract: Transportation is an important resource for the sustainable development of the Qinghai-Tibet Plateau. It is of great practical significance to evaluate and study the law and mechanism of spatial and temporal differentiation of traffic dominance degree. Based on the methods of the Origin-Destination cost matrix, least squares method, and geographically weighted regression, this paper establishes a traffic dominance evaluation system at the county scale and discusses the spatial pattern and influence of traffic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Consistent with the findings of existing research, this paper found that both territorial and potential accessibility tend to be unequal, which reveals that there are still many deficiencies in of accessibility in Tibet at the rapid development stage of transportation construction here (Gao et al., 2019; Wang et al., 2022; Wang et al., 2022b). However, there is still different from the conclusion that the fairness of accessibility at township level is declining (Gao & Sun, 2022).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the findings of existing research, this paper found that both territorial and potential accessibility tend to be unequal, which reveals that there are still many deficiencies in of accessibility in Tibet at the rapid development stage of transportation construction here (Gao et al., 2019; Wang et al., 2022; Wang et al., 2022b). However, there is still different from the conclusion that the fairness of accessibility at township level is declining (Gao & Sun, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…The fairness of transport accessibility is an important condition for realizing the sustainable development of Tibet (Gao & Sun, 2022; Wang et al., 2022). The findings of this study may provide reference to the areas in the world which features a unique natural environment and vulnerable ecological environment as well as the areas with slow social development, sparse population density, and multiple ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, many scholars applied and further developed TSD assessments in regions with diverse characteristics, including provinces [5], counties [6], rural areas [7], and mountainous terrain [8]. Notable advancements have centered around the following: improved indicator selection: various indicators have been developed to address specific issues, such as accessibility to different transportation modes [9], weighted shortest distance [10], road traffic volume [11], and population density weighting [12]. These indicators aim to capture the nuances of regional transportation service supply and demand; enhanced calculation accuracy: evaluations have been refined by considering factors such as airports [9], seaports [5], proximity to highways and their exits [13], and incorporating terrain correction coefficients or terrain impact factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Notable advancements have centered around the following: improved indicator selection: various indicators have been developed to address specific issues, such as accessibility to different transportation modes [9], weighted shortest distance [10], road traffic volume [11], and population density weighting [12]. These indicators aim to capture the nuances of regional transportation service supply and demand; enhanced calculation accuracy: evaluations have been refined by considering factors such as airports [9], seaports [5], proximity to highways and their exits [13], and incorporating terrain correction coefficients or terrain impact factors [8]. These refinements ensure that assessments better reflect real-world conditions, particularly in regions with significant terrain variations; and adapting to transportation trends: the discussion of regional TSD now incorporates considerations of rapid transportation, especially high-speed rail development [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…In urban infrastructure, the city transportation network is complex and intricate, serving as a necessary prerequisite and crucial support for regional socio-economic development [1,2]. It is the precursor and core of regional development and urban structure shaping [3], determining residents' quality of life and the sustainable development of the city.…”
Section: Introductionmentioning
confidence: 99%